Understanding geographies of polarization and peripheralization perspectives from Central and Eastern Europe and beyond - Lang, Thilo 1941-; Henn, Sebastian 1977-; Sgibnev, Wladimir 1983-; Ehrlich, Kornelia (New geographies of Europe, 2015)
"Spatial disparities in Central and Eastern Europe have been intensifying for more than two decades, yet little is known about the socio-spatial developments leading to these geographical changes. By putting the concepts of polarization and peripheralization at its centre, this book presents a multifaceted perspective on regional development and the ways we register, survey and conceptualize spatial phenomena, such as the emergence, persistence and transformation of spatial disparities and socio-spatial inequalities. Understanding Geographies of Polarization and Peripheralization discusses both theoretical and empirical approaches, presenting several compelling case studies from Central and Eastern Europe and beyond. This book provides relevant insights for readers from all parts of the world and is of particular interest for researchers and practitioners, as well as graduate and postdoctoral students, in the fields of Regional Development, Geography, Spatial Planning, European and Area Studies"..